Evaluating political accountability in water projects with the aim of determining the impact of political accountability on project sustainability. - Bezuidenhout, Lydia (Stellenbosch : University of Stellenbosch, 2009)
Thesis (MA (Political Science))--University of Stellenbosch, 2009.